Formation and development of scientific journalism in Belarus: theoretical and applied aspect - Lukyaniuk, Yuliya M. (Journal of the Belarusian State University. Journalism, 2023)
The issues of the formation of scientific (popular science) journalism as a systemic phenomenon of the domestic media process are considered. The specifics of the formation and development of scientific journalism in Belarus are substantiated. It is determined that scientific journalism is a complex of mass media, which includes periodic regional, republican and international publications of a single thematic focus. The pre-Soviet, Soviet and post-Soviet stages of the development of science journalism in Belarus are distinguished. At the pre-Soviet stage of development, scientific journalism was focused on regional needs and local socio-economic conditions, the development of a scientific, theoretical and practical base, the formation of a mass audience through the publication of popular science articles and practical recommendations for non-specialists in a particular scientific field, a review of scientific discoveries. At the Soviet stage of development, the main direction of science journalism was the popularisation of basic knowledge of fundamental sciences. At the post-Soviet stage, scientific journalism focused on the coverage of economic problems, issues related to leisure and traditional medicine. Since the early 2000s the circulation of newspapers and magazines is gradually decreasing, interest in scientific topics is decreasing, the audience joins watching entertainment programs on television and in social networks, which contributes to the departure of printed publications to the online format.